Utility of Phatak’s Repertory in Acute Cases: An Open Observational Clinical Trial (Advancements in Homeopathic Research, 2022)
Context: In Homoeopathic parlance, Phatak’s Repertory is considered as a useful tool for accurate prescribing in acute cases, there is a need to validate this perception.Aim: The aim of the study was to evaluate the utility of Phatak’s repertory in acute cases.Methods: An open-label, prospective, observational, non-controlled clinical trial was conducted at Dr. Madan Pratap Khunteta Homoeopathic Medical College, Hospital & Research Centre and Homoeopathy University Hospital, Jaipur with approval of the institutional ethics committee. The follow-up of the patients was done as per gravity of the case. Per Protocol analysis of the outcomes was done using four point grading scale - marked, mild improvement, status quo and worse. Remedies were prescribed in consultation with Phatak’s repertory following homoeopathic principles.Results: Fifty four subjects were enrolled and only fifty patients completed the trial, which were analysed per protocol (n = 50). Majority of patients (n = 41, 82%) reported marked improvement, few patients (n = 3, 6%) reported mild improvement, while only 10%were status quo and 2% fell in worse category. Pulsatilla nigricans, Nux Vomica, Rhus toxicodendron and Sepia (n = 5 each, 10%) were prescribed frequently. 105 rubrics in respect of 26 remedies in 18 diseases were validated.Conclusion: Phatak’s repertory is indeed a useful tool for efficient and quick acute prescribing. Since acute diseases have self-limiting course, the outcomes need to be further validated with large sample size and another comparative group or using pragmatic trials.
Keywords: Acute cases; Dr. S. R. Phatak; Homoeopathy; Phatak’s repertory; Repertory